2014
DOI: 10.1523/jneurosci.4063-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Control Disorders in Parkinson's Disease Are Associated with Dysfunction in Stimulus Valuation But Not Action Valuation

Abstract: A substantial subset of Parkinson's disease (PD) patients suffers from impulse control disorders (ICDs), which are side effects of dopaminergic medication. Dopamine plays a key role in reinforcement learning processes. One class of reinforcement learning models, known as the actor-critic model, suggests that two components are involved in these reinforcement learning processes: a critic, which estimates values of stimuli and calculates prediction errors, and an actor, which estimates values of potential action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 53 publications
8
75
0
Order By: Relevance
“…Individuals with a history of self-reported cocaine use also responded in a way that was qualitatively similar to cocaine users in the laboratory sample from Experiment 1. Control participants did not show suboptimal performance, consistent with previous studies in healthy, non-clinical populations (e.g., Bodi et al, 2009; Herzallah et al, 2013; Piray et al, 2014; Somlai et al, 2011). These differences were observed after controlling for demographic factors indicating that this effect was likely not the result of other differences between these groups.…”
Section: Discussion: Experimentssupporting
confidence: 89%
See 2 more Smart Citations
“…Individuals with a history of self-reported cocaine use also responded in a way that was qualitatively similar to cocaine users in the laboratory sample from Experiment 1. Control participants did not show suboptimal performance, consistent with previous studies in healthy, non-clinical populations (e.g., Bodi et al, 2009; Herzallah et al, 2013; Piray et al, 2014; Somlai et al, 2011). These differences were observed after controlling for demographic factors indicating that this effect was likely not the result of other differences between these groups.…”
Section: Discussion: Experimentssupporting
confidence: 89%
“…Previous studies have also shown decreased learning from positive outcomes in non-medicated Parkinson’s patients (Bodi et al, 2009; Piray et al, 2014). Parkinson’s disease is characterized by neuronal death and disruptions in dopaminergic signaling in areas of the brain involved in reinforcement learning, including the mesocorticolimbic region in addition to characteristic damage along the nigrostriatal pathway (Jellinger, 1991).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As noted above, RL theories assume that learning is based on a prediction error signal that is used to update the learner’s expectations and guide action selection; PE may be encoded by nigrostriatal dopamine (38); targets in the ventral striatum then use these signals to update predictions and guide learning (39). Piray et al (40) examined patients with Parkinson’s disease, a disorder that involves progressive cell loss in the ventral striatum, who had also developed impulse control disorders. When these patients were tested on their normal dopaminergic medication, the patients showed enhanced reward learning, but impaired punishment learning, relative to matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PD patients without ICDs showed no difference between reward and punishment learning (Balasubramani et al ., 2015). In another study, PD patients with ICDs were shown to exhibit hyposensitivity to loss (Piray et al ., 2014). Multiple studies have demonstrated that dopaminergic medications in PD patients—highly associated with ICDs—prevents learning from negative decision outcomes (Frank, 2006) (Frank, 2005) (Cools et al ., 2006) (Frank and O’Reilly, 2006).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%